Lake seasonality across the Tibetan Plateau and their varying relationship with regional mass changes and local hydrology. Issue 2 (17th January 2017) - Lei, Yanbin; Yao, Tandong; Yang, Kun; Sheng, Yongwei; Kleinherenbrink, Marcel; Yi, Shuang; Bird, Broxton W.; Zhang, Xiaowen; Zhu, La; Zhang, Guoqing
Abstract: The recent growth and deepening of inland lakes in the Tibetan Plateau (TP) may be a salient indicator of the consequences of climate change. The seasonal dynamics of these lakes is poorly understood despite this being potentially crucial for disentangling contributions from glacier melt and precipitation, which are all sensitive to climate, to lake water budget. Using in situ observations, satellite altimetry and gravimetry data, we identified two patterns of lake level seasonality. In the central, northern, and northeastern TP, lake levels are characterized by considerable increases during warm seasons and decreases during cold seasons, which is consistent with regional mass changes related to monsoon precipitation and evaporation. In the northwestern TP, however, lake levels exhibit dramatic increases during both warm and cold seasons, which deviate from regional mass changes. This appears to be more connected with high spring snowfall and large summer glacier melt. The variable lake level response to different drivers indicates heterogeneous sensitivity to climate change between the northwestern TP and other regions. Key Points: Two patterns of lake level seasonality between the northwestern TP and the other regions are identified Lake level variations in the central, northern, and northeastern TP are consistent with regional total mass changes Lake level variations in the northwestern TP deviate from regional total mass changes